PKM Pembuatan Nugget Ikan Fortifikasi Daun Kelor Sebagai Bahan Pangan Tinggi Protein - Ramli, Hartini; Andi Sukainah; Puspitasari, Dewi; Lahming; Jayanegara, Sudarmanto (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
Assistance activities for processing fish nuggets with the addition of moringa for the community in Limbua Village, Sendana District, Majene Regency with the hope of supporting government programs in improving people's welfare and obtaining healthy food preparations, increasing the knowledge and skills of participants in processing fish nuggets with the addition of Moringa as a healthy food ingredient. Implementation of activities carried out in three stages; stage one is observation of activity locations, stage two is the stage of implementing PKM activities, and stage three is the final stage of the activity, in this stage an evaluation is carried out. This activity was attended by 60 participants. After participating in this activity, the community, especially PKH women and housewives in Limbua Village, have a good understanding of how to process fish nuggets with the addition of moringa. The results obtained from this activity were prior to the activity, knowledge of processing fish nuggets, partners had never made their own nuggets. This is because partners do not know how to make it. After the counseling and practice activities, the respondents' knowledge about making fish nuggets and how to process them increased.